Biology and Demographic Statistic Myzus persicae on Chili Plant - Fadloli, Ahmad Iqbal Rijal; Rahardjo, Bambang Tri (Journal of Tropical Plant Protection, 2024)
This research aimed to observe the biological aspects and demographic data of Myzus persicae on chili plants. The research was conducted at the Laboratory of Pests and Wire House, Department of Plant Pests and Diseases, Faculty of Agriculture, Brawijaya University, Malang, from August 2020 to July 2021. Biological observations, including the life cycle, lifespan, and fecundity, were made to gather demographic data. Parameters for demographic analysis included the gross reproduction rate (GRR), net reproduction rate (R0), intrinsic rate of increase (r), and generation time (T). The results showed that the nymphal stages lasted 2.30, 2.17, 2.28, and 2.09 days for the first to fourth instars, respectively. The mean life cycle duration was 8.85 days, with a total fecundity of 21.04 offspring per female adult. Meanwhile, the average lifespan of M. persicae was 11.93 days. Demographic statistics for M. persicae on chili showed a GRR of 51.71 individuals per generation, an R0 of 14.41 individuals per female per generation, an r of 0.38 individuals per female per day, and a T of 16.22 days.